The Image of a Historical Personality in the Urban Sculptural Monument in St. Petersburg at the Turn of the 20th – 21st Centuries: Applying Textual Analysis - Gorlenko, Alina S. (Actual Problems of Theory and History of Art, 2013)
The article presents an attempt to analyze textually the monuments to the rulers, namely the monument to Emperor Peter I and the monument to Emperor Paul I and to the so-called “artists of the word”— the monument to Fyodor M. Dostoevsky and the monument to Anna A. Akhmatova erected according to the environmental approach in St. Petersburg during the period of 1990‒2010. The textual analysis is based on the correlation of artistic, cultural and historical “texts” of the sculptural surface and the site of architectural space with intellectual, spiritual and emotional “texts” of a person perceiving them. The understanding of the conception of the sculptural monuments made it possible to interpret the embodiment of every historical figure as a personified genius loci.
Keywords: monument; sculpture; urban environment; environmental approach; the image of the environment; textual analysis; genius loci; “spirit of place”; the image of a historical person